An investigation of adherence to best practice guidelines for autism diagnosis in New Zealand. (October 2021) - Taylor, Lauren J; Eggleston, Matthew JF; Thabrew, Hiran; van der Meer, Larah; Waddington, Hannah; Whitehouse, Andrew JO; Evans, Kiah
Recent studies of autism diagnosis in New Zealand have revealed inconsistent implementation of best practice standards in autism assessment and high rates of parental dissatisfaction with the diagnostic process. These findings have arisen despite the development and dissemination of the New Zealand Autism Spectrum Disorder Guideline (the Guideline). In this study, we investigated current diagnostic processes, and adherence to the Guideline in New Zealand, for an opportunity sample of 117 health professionals who practice across a wide range of diagnostic services, health professionals and geographic regions in New Zealand. The results show considerable variability in practice, and suggest specific areas for improvement. These include the robustness of diagnostic evaluations conducted in private settings, the provision of specialist assessment services for youth and adults presenting for autism diagnosis, and the uniformity of post-diagnostic supports and services. These findings have implications for further implementation of the Guideline in New Zealand. Lay abstract: Many clinicians in New Zealand do not follow guidelines for best practice in autism diagnosis. In this study, we investigated the processes that health professionals in New Zealand follow when diagnosing autistic children and adults. We asked 117 health professionals from a range of services and regions in New Zealand, how they identify and diagnose autism. We found that there are differences in the way that clinicians in New Zealand diagnose autism. We identified areas in which autism diagnosis in New Zealand could be improved, for example, by establishing more services to diagnose autism in adolescents and adults, and providing more consistent support after a person is diagnosed with autism. These findings will help to improve autism diagnosis in New Zealand.